Morphology Inflorescence and Anther Anatomy of Musa campestris var. sarawakensis from West Kalimantan, Indonesia - Ari Sunandar; Hayatul Fajri; Mahwar Qurbaniah (Postgraduate, University of Mataram, 2023)
Musa campestris is a unique banana, has erect inflorescence with beautiful bracts and mature fruit colors so that it can be used as an ornamental plant. this study's objective is to analyze the morphological inflorescences and anther anatomical characteristics of theÂ Musa campestris var. sarawakensis. Plant materials were collected in Sanggau regency. Morphological characterizations were conducted using International Plant Genetic Resources Institute for Musa spp. Sampel of anther was prepared using paraffin method, stained with 2% safranin and 1% fast green. Main features observed for Musa campestris var. sarawakensis inflorescence has erect rachis position and color external bract are helpful to characterize the male bud. Additionally, the main characteristics of anther include the presence helical ribs in endothecium. As expected, tetrasporangiate anthers with single vascular bundle in male flowers was observed. The main morphology characteristics of inflorescence and anther anatomy of Musa campestris var. sarawakensis are highlighted in this study, contributing to provide more information about the characterization of this species in West Kalimantan.